Bringing the (Pre)Registration Revolution to Graduate Training. - Tackett, Jennifer L.; Brandes, Cassandra M.; Dworak, Elizabeth M.; Shields, Allison N. (Canadian Psychology / Psychologie Canadienne, 2020)
Preregistration, which involves documentation of hypotheses, methods, and plans for data analysis prior to data collection or analysis, has been lauded as 1 potential solution to the replication crisis in psychological science. Yet, many researchers have been slow to adopt preregistration, and the next generation of researchers is offered little formalized instruction in creating comprehensive preregistrations. In this article, we describe a collaborative workshop-based preregistration course designed and taught by Jennifer L. Tackett. We provide a brief overview of preregistration, including resources available, common concerns with preregistration, and responses to these concerns. We then describe the goals, structure, and evolution of our preregistration course and provide examples of enrolled students' final research products. We conclude with reflections on the strengths and opportunities for growth for the 1st iteration of this course and suggestions for others who are interested in implementing similar open science--focused courses in their training programs.